2009
DOI: 10.1118/1.3116902
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a variable dose acquisition technique for microcalcification and mass detection in digital breast tomosynthesis

Abstract: In this article the authors evaluate a recently proposed variable dose ͑VD͒-digital breast tomosynthesis ͑DBT͒ acquisition technique in terms of the detection accuracy for breast masses and microcalcification ͑MC͒ clusters. With this technique, approximately half of the total dose is used for one center projection and the remaining dose is split among the other tomosynthesis projection views. This acquisition method would yield both a projection view and a reconstruction view. One of the aims of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…These observations suggested that DBT was unlikely to be used as a stand-alone imaging modality if a 2D mammogram was required for optimal microcalcification assessment. 25,52,53 Cancer detection and recall rate…”
Section: Diagnostic Accuracymentioning
confidence: 99%
“…These observations suggested that DBT was unlikely to be used as a stand-alone imaging modality if a 2D mammogram was required for optimal microcalcification assessment. 25,52,53 Cancer detection and recall rate…”
Section: Diagnostic Accuracymentioning
confidence: 99%
“…Dose levels between 1.6 mGy [53] and 4 mGy [54] have been reported. The total tube loading (mAs value) is often divided equally among the projection images [55], but recently the effect of spending a larger fraction of the total dose on the center projection in order to increase detection of microcalcifications have been investigated [56][57][58]. Spangler et al [59] did not find any difference in area under the receiver operating characteristic (ROC) curve [60] for BI-RADS (breast imaging reporting and data system) scores of calcifications for DM and BT, although they found a higher sensitivity for calcification detection.…”
Section: Technical Aspects Of Bt Image Volume Acquisitionmentioning
confidence: 99%
“…The contributions of the homogeneous parts of the volume are then placed outside of the smoothing kernel in equation (5), with b sθ the total blank value for angle θ and w θϕ the normalized waveform of the exposure at angle θ. The key approximation is then applied in (6) where the sum over the sparsely sampled angles with kernel w θϕ is replaced by a sum over the densely sampled detector pixels with kernel w P nξ , which is combined with kernel A sn to form A P sn in (7). At this point we can assume that there are more high contrast lesions in the volume, but that they don't overlap in the projections.…”
Section: A Resolution Modelmentioning
confidence: 99%
“…One path to improve visualization of microcalcifications is to optimize the dose and angular distribution of the limited angle set of projections [7][8][9]. These projections are then usually reconstructed with filtered backprojection (FBP) although this reconstruction by FBP is not always optimal [10,11] because of the limited angular range and low dose acquisitions, * koen.michielsen@uzleuven.be especially for small angular range [12].…”
Section: Introductionmentioning
confidence: 99%